Learner digital identity development within authentic pedagogy of foreign language acquisition - N. L. Moskovskaya; E. A. Perova (Вестник Северо-Кавказского федерального университета, 2023)
The relevance of the chosen topic is due to the need to develop an authentic or genuine learner identity in the era of intensive digitalization and polyculturalization of society. This study is aimed at analyzing the multiple variety of learner identities in digital space that are developed through the implementation of socially and personally sound interactive contexts and web technologies. The article explores the specificity of digital literacy formation as an essential core of the cognitive behavioral and individual model of authentic pedagogy. As a result of the study, it was revealed that authentic pedagogy as well as linguodidactics can become a conceptual basis for the construction of a genuine and unique digital identity as a new modality of social and professional self-actualization within unforced communicative activity aimed at creating a unique intellectual property. The authors conclude that the self-representation of a unique media image in the foreign language digital realm is implemented by adhering to such essential principles of authentic pedagogy as communication, cognition, prosociality, interactivity and personal freedom.